2009
DOI: 10.1021/ac9004106
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Cavity Enhanced Absorption Spectroscopy as a Detector for HPLC

Abstract: The first demonstration of a cavity enhanced absorption spectroscopy (CEAS) based technique, applied to HPLC detection is reported. Broadband cavity enhanced absorption spectroscopy (BBCEAS) has been used for detection in a HPLC system (HPLC-BBCEAS). Measurements were made on the dyes rhodamine 6G and rhodamine B between 450 and 600 nm. The sensitivity of the measurements as determined by the minimum detectable change in the absorption coefficient, alpha(min), were 2.9 x 10(-5) cm(-1) at 527 nm and 1.9 x 10(-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…There are clear advantages in having this capability: to measure several compounds simultaneously and to increase the amount of information in a particular measurement, thereby statistically enhancing the output (for example, in measuring several spectral lines to record an isotopic ratio); and to improve specificity, where target species exhibit relatively broad spectral signatures. Several schemes have been reported for BB-CEAS involving different sources and detection apparatus, and including application to the measurement of liquid and/or surface borne species [10,13,14,15,18,19]. On the whole, these studies have been at visible wavelengths, and as broad band optical sources both light emitting diodes and discharge lamps have featured predominantly and have been used with either imaging spectrometers or Fourier transform interferometers as detection systems.…”
Section: Introductionmentioning
confidence: 99%
“…There are clear advantages in having this capability: to measure several compounds simultaneously and to increase the amount of information in a particular measurement, thereby statistically enhancing the output (for example, in measuring several spectral lines to record an isotopic ratio); and to improve specificity, where target species exhibit relatively broad spectral signatures. Several schemes have been reported for BB-CEAS involving different sources and detection apparatus, and including application to the measurement of liquid and/or surface borne species [10,13,14,15,18,19]. On the whole, these studies have been at visible wavelengths, and as broad band optical sources both light emitting diodes and discharge lamps have featured predominantly and have been used with either imaging spectrometers or Fourier transform interferometers as detection systems.…”
Section: Introductionmentioning
confidence: 99%
“…those techniques that utilise broad-band emission sources, are increasing in popularity where it is desirable either to measure several compounds simultaneously that absorb in different spectral regions or where specificity is required for target species with extended absorption features (such as relatively large molecules or surface/liquid-borne species). Several studies have been reported that combine different broad-band sources such as arc-lamps [1][2][3][4][5][6] and light emitting diodes (LEDs) [7][8][9][10][11][12] with dispersive and interferometric detection schemes to detect gas phase species such as iodine oxides, 5 NO x compounds, 7,8,10,11 and solutions containing dyes (e.g. coumarin 334, brilliant blue-R, and rhodamine B and 6G) 9,12,13 which absorb at visible wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported that combine different broad-band sources such as arc-lamps [1][2][3][4][5][6] and light emitting diodes (LEDs) [7][8][9][10][11][12] with dispersive and interferometric detection schemes to detect gas phase species such as iodine oxides, 5 NO x compounds, 7,8,10,11 and solutions containing dyes (e.g. coumarin 334, brilliant blue-R, and rhodamine B and 6G) 9,12,13 which absorb at visible wavelengths. High power supercontinuum sources have also been demonstrated in cavity enhanced spectroscopy, 14,15 but these are devices that represent a major financial investment, generate a wide spectral output, usually much larger than the stop band of the high reflectivity cavity mirrors, and generally have optimised performance in the visible and near-IR (<1 mm).…”
Section: Introductionmentioning
confidence: 99%
“…25 The estimated limit of detection for acetone is higher than the range found in healthy breath (390 to 850 ppbv), but further improvements in sensitivity could make this approach practical for breath analysis. Other applications include detectors for chromatography, for which both CRDS 26,27 and CEAS 28 have previously been proposed. Although this work has focussed on gases, the approach is also feasible for liquid samples.…”
Section: Resultsmentioning
confidence: 99%